2017
DOI: 10.2147/ppa.s123723
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the feasibility of text message reminders to improve adherence to nebulized medication in children and adolescents with cystic fibrosis

Abstract: BackgroundChildren with cystic fibrosis (CF) often have suboptimal adherence rates to nebulized medication. Adherence barriers cited include forgetting to take the nebulizers, due to busy home and social lives. Text message reminders have been shown to be effective at improving adherence rates in other chronic diseases such as asthma and diabetes.ObjectiveThe objective of this study was to assess the feasibility and efficacy of sending text reminders for a prolonged period of time to children with CF.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Many of the same studies that elicited the aforementioned barriers have also identified multiple adherence motivators such as recognition of the impact of non‐adherence on health outcomes, a strong relationship with the CF care team and encouragement from friends and family . Interventions that promote self‐management skills, whether they be a knowledge‐based intervention such as providing more education about the disease process and available treatments, or a behavioral intervention like motivational interviewing, appear to improve medication adherence in individuals with CF . The use of technology to promote self‐management skills and adherence is becoming increasingly popular .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the same studies that elicited the aforementioned barriers have also identified multiple adherence motivators such as recognition of the impact of non‐adherence on health outcomes, a strong relationship with the CF care team and encouragement from friends and family . Interventions that promote self‐management skills, whether they be a knowledge‐based intervention such as providing more education about the disease process and available treatments, or a behavioral intervention like motivational interviewing, appear to improve medication adherence in individuals with CF . The use of technology to promote self‐management skills and adherence is becoming increasingly popular .…”
Section: Introductionmentioning
confidence: 99%
“…Interventions that promote self‐management skills, whether they be a knowledge‐based intervention such as providing more education about the disease process and available treatments, or a behavioral intervention like motivational interviewing, appear to improve medication adherence in individuals with CF . The use of technology to promote self‐management skills and adherence is becoming increasingly popular . Medication reminders have been successful in enabling patients with CF to take ownership of their disease and have resulted in improved adherence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For over 10 years, mobile phone technology has been used in the management of chronic disease with applications such as appointment reminders and short message service (SMS) prompts to take medication (78,79). Within asthma alone, webbased programmes have also been used to facilitate decisionmaking via self-help algorithms.…”
Section: Smart Technology To Optimize Asthma Controlmentioning
confidence: 99%
“…To address the need for optimised adherence to maintenance medication in patients with respiratory diseases, a number of digital technologies have been developed. Strategies used to date include approaches to monitoring and improving adherence, such as electronic inhalers, text messaging and reminders, and self-management tools (such as web-based and mobile applications to record symptoms and monitor lung function) [58]. Examples of digital interventions targeting adherence in patients with asthma and COPD that were published between 2007 and 2017, including electronic monitoring devices (EMDs), text messaging, and web and mobile applications, are summarised in table 1.…”
Section: Current and Emerging Digital Technologies In Respiratory Medmentioning
confidence: 99%